DEVICE-TO-DEVICE COMMUNICATIONS DIRECTION FOR DISASTER MANAGEMENT: A REVIEW - Norhisham Mansor; Wahidah Md Shah; Najwan Khambari (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Communications in disaster management is crucial and vital to save lives. This study highlights the significant roles and impacts of Device-to-Device (D2D) communications in disaster management. The study utilizes the Web of Science (WoS) and Scopus databases, focusing on literature that explores D2D technology’s application in disaster situations. The study reveals that an ample portion of the research concentrates on energy efficiency, underlining its prominence in D2D applications. Maintaining low energy consumption remains a challenge to enable reliable communications in disaster. Future research directions exhibit a promising trend towards integrating D2D with emerging technologies like the Internet of Things (IoT) and Unmanned Aerial Vehicles (UAVs) for enhanced disaster communication. This study underlines the need for continued development and implementation of D2D technologies in disaster management, contributing to saving lives and reducing the impact of disasters.